The Contribution of Kampus Mengajar Program to the Students’ Personal Development and Employability - Suranto Suranto; Rochman Hadi Mustofa; Dhany Efita Sari; Titik Ulfatun; Jonathan Camana Gano-an; Bunga Amanda (STAI Hubbulwathan Duri, 2023)
This research aimed to examine the effect of Kampus Mengajar program experience on personal development and employability, with the usefulness of the program as an intervening variable. This study applied the quantitative method with causality research design and the Structural Equation Model (SEM) for the research analysis approach. The data collection technique used the Likert scale questionnaires sent through a Google form. 62 students of the Accounting Education Study Program joined Kampus Mengajar program Batch 1 and Batch 2. The data were analyzed by software SmartPLS 3 with a Partial Least Square (PLS) approach. The first step of the analysis was model measurement, which consisted of construct reliability, construct validity, and discriminant validity. The second step was structural model measurement to examine the hypotheses which comprised of R2 value, f2 value, direct effect, and indirect effect. The result revealed a direct and significant effect of Kampus Mengajar experience on program's usefulness. Besides, Kampus Mengajar experience showed an immediate and significant effect on each personal development and employability variable. Another research result showed an indirect significant effect of Kampus Mengajar experience on personal development with the program's usefulness as an intervening variable. This study concludes that Kampus Mengajar program as a teaching internship program positively influences students, and thus, this program needs to be followed up.